2019
DOI: 10.3390/brainsci10010018
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin Hp1 Variant Does Not Associate with Small Vessel Disease

Abstract: Haptoglobin (Hp) is a plasma protein that binds free hemoglobin and protects tissues from oxidative damage. An Hp2 allele has been associated with an increased risk of cardiovascular complications. On the other hand, recent studies have suggested that Hp1 allele increases risk to develop severe cerebral small vessel disease. We aimed to replicate this finding in a first-ever stroke patient cohort. Hp was genotyped by PCR and gel electrophoresis in the Helsinki Stroke Aging Memory Study in patients with DNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Our results, however, agree with previous studies in individuals without diabetes, where no association between Hp-genotype and cerebral SVD were reported [ 23 , 30 ]. Nevertheless, findings have been contradictory also in individuals without diabetes and one previous study linked the genotype Hp1-1 to larger volumes of white matter hyperintensities [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results, however, agree with previous studies in individuals without diabetes, where no association between Hp-genotype and cerebral SVD were reported [ 23 , 30 ]. Nevertheless, findings have been contradictory also in individuals without diabetes and one previous study linked the genotype Hp1-1 to larger volumes of white matter hyperintensities [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, findings have been contradictory also in individuals without diabetes and one previous study linked the genotype Hp1-1 to larger volumes of white matter hyperintensities [ 31 ]. Reports on the association between Hp-genotype and lacunar infarctions are likewise contradictory [ 21 , 30 ], while, to the best of our knowledge, no studies on cerebral microbleeds exist.…”
Section: Discussionmentioning
confidence: 99%
“…Hb-HP was increased in the HDL of atherogenic/hyperlipidemic mice and in the HDL of individuals with CAD ( 29 ) and the amount of Hb bound to HDL correlates with the proinflammatory properties of dysfunctional HDL ( 29 ). Recently, a study reported that HP regulates vascular health through several means ( 30 ). Strikingly, we found that, compared to healthy participants, HP expression levels were significantly downregulated in stable CAD and ACS patients, which is inconsistent with the previous study; in animal models of myocardial ischemia, the HP protein has been implicated in coronary collateral development ( 31 ); Jahagirdar et al ( 25 ) found that HP protein levels were significantly upregulated in humans with cardiovascular disease, and HDL isolated from mice lacking this protein was involved in anti-inflammatory activity compared to Wild-type mice.…”
Section: Discussionmentioning
confidence: 99%